Role of Microfinance in Poverty Alleviation in the Least Developed Area of Pakistan - Ullah, Atta; Pinglu, Chen; Ullah, Saif; Aslam, Noman; Zaman, Mubasher (Asian Economic and Financial Review, 2020)
Microfinance is regarded as a tool to support the reduction of poverty and this study aims to determine its effect on poverty alleviation in the least developed area of Pakistan. The study is based on primary data collected from a sample of 250 less-educated people who had availed themselves of MFI services, and regression and crosstab analyses performed to assess the performance of microfinance in meeting basic needs, improving living standards, and the usage of microfinance to enhance income levels. The results revealed a significant, positive relationship between microfinance and poverty alleviation. The study recommends that MFIs should offer training sessions before advancing credit as most of the clients may not be well educated or skilled and need entrepreneurial skills, business knowledge, and guidance.